Introduction #6 - Julie Abbou; Aron Arnold; Sophie Bailly; Maria Candea; Mona Gérardin-Laverge; Magali Guaresi; Noémie Marignier (Glad!)
This sixth issue of GLAD! is a varia issue with a strong topical coherence: in the "Research" section, the articles explore forms of feminist and queer artistic and cultural resistance in different contexts (North America, Latin America, Europe, Africa) involving various means of expression (cinema, literature, visual arts). The "Creations" section, which provides two original literary works, playing in a feminist and subversive way with and about the language, echoes these scientific articles in a beautiful way. The "News" section is enriched with several reviews and thesis summaries that illustrate the variety and dynamism of French gender and language studies, and the "Chronicle" section highlights the political dimension of these studies by discussing the issue of the practice of changing first names.